The Long-Term Effectiveness of Psychoeducation for Bipolar Disorders in Mental Health Services. A 4-Year Follow-Up Study - Buizza, Chiara; Candini, Valentina; Ferrari, Clarissa; Ghilardi, Alberto; Saviotti, Francesco Maria; Turrina, Cesare; Nobili, Gianluigi; Sabaudo, Margherita; de Girolamo, Giovanni (Frontiers in Psychiatry, 2019)
Aims: The aims of the present study were to assess: the effectiveness of psychoeducation in mental health service (MHSs) in terms of time to first hospitalization during 4-year follow-up; the number and the days of hospitalizations, and the number of people hospitalized at 4-year follow-up; and variables associated with better outcome in BD patients. Methods: This is a controlled study involving an experimental group (N = 57) and a control group (N = 52). The treatment phase consists of 21 weeks, in which all participants received TAU, while the experimental group received additional psychoeducation. Results: The survival analysis showed significant differences in terms of time to first hospitalization of up to 4-year follow-up: the patients in the psychoeducation group showed a longer time free from hospitalizations than the control group. Concerning the predictors of time to first hospitalization, the only factor that showed a trend to statistical significance was psychoeducation. Conclusions: This is one of few studies assessing the long-term effectiveness of psychoeducation in a naturalistic setting. The data confirm that psychoeducation can impact illness course, in terms of longer time free from hospitalizations. Trial registration: ISRCTN17827459